Potential coverage of the 4CMenB vaccine against invasive serogroup B Neisseria meningitidis isolated from 2009 to 2013 in the Republic of Ireland - Mulhall, R; Bennett, D; Cunney, R; Borrow, R; Lucidarme, J; Findlow, J; Jolley, K; Bray, J; Maiden, M; Moschioni, M; Serino, L; Stella, M; et al. (American Society for Microbiology, 2018)
Neisseria meningitidis is a common cause of bacterial meningitis in children and young adults worldwide. The 4CMenB vaccine (Bexsero), developed to combat meningococcal serogroup B (MenB) disease, contains subcapsular antigens that may induce immunity against strains of N. meningitidis, regardless of serogroup. Owing to differential levels of expression and peptide diversity in vaccine antigens across meningococcal strains, the meningococcal antigen typing system (MATS) was developed to estimate the potential MenB strain coverage of 4CMenB. Prior to introducing the 4CMenB vaccine into routine use, we sought to estimate the potential 4CMenB coverage against invasive MenB strains isolated in the Republic of Ireland (RoI) over four consecutive epidemiological years. MATS was applied to a panel of 105 invasive MenB strains isolated during July 2009 to June 2013. Sequence data characterizing the multilocus sequence typing (MLST) alleles and the major 4CMenB target peptides were extracted from isolate genome sequence data, hosted in the Bacterial Isolate Sequencing database (BIGSdb). MATS data indicated that 4CMenB may induce protective immunity against 69.5% (95% confidence interval [CI95%], 64.8% to 84.8%) of circulating MenB strains. Estimated coverage was highest against the most prevalent disease-causing lineage, cc41/44, where the most frequently observed sequence types, ST-154 and ST-41 (21% of isolates, collectively), were typically covered by three antigens. No significant temporal trends were observed. Overall, these data provide a baseline of strain coverage prior to the introduction of 4CMenB and indicate that a decrease in invasive meningococcal disease (IMD) is predicted following the introduction of 4CMenB into the routine infant immunization schedule in the RoI.